Challenges and response in islamic education perspective in the digital media era - Hasbi Indra (IAIN Salatiga, 2020)
This study aims to discuss the challenges and responses of Islamic schools in the digital era, which is characterized by human dependence on technology as the digital tool needed in their life so that one effect is a disruption in all social space. Islamic schools, as one kind of Islamic education, are established by the government and the community to provide a human resource in the nation. This institution is part of the national education system and becomes part of measuring the quality of national education. As part of human resources in the society facing trade, international competition between countries is still ongoing, such as GATT, NAFTA, and AEC, and in this era, students face the problems of disruption in all spaces, where robots substitute many fields. This education must ready to respond to the challenges and difficulties. In this era, learning requires students to have broader knowledge, science, economics, entrepreneurial spirit, competence, and good character. Islamic schools can be formed through educational instruments such as curriculum, and teachers must have broader knowledge, abilities, and so on